Constructing Postcolonial Muslim Identity: A Dual-Theory Framework of Qur'anic Learning in Indonesia - Agus Sriyanto; Ahmad Rafiq; Suyadi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This research examines the construction of religious identity through decolonization in Qur'anic learning in postcolonial Indonesia by integrating Berger and Luckmann's Social Construction Theory and Tajfel and Turner's Social Identity Theory within a decolonial framework. Through a systematic literature review of 53 peer-reviewed academic publications (2014-2025) selected through purposive sampling based on relevance to Qur'an pedagogy, identity formation, and decolonial discourse in Indonesia, this study employs thematic analysis within an interpretive, qualitative, and postcolonial approach. Identity formation operates through three mechanisms: externalization of religious values, objectivation in Islamic institutions, and transformative internalization. Decolonization strategies emerge through epistemological reintegration and pedagogical contextualization that bridge Qur'an teachings with the contemporary reality of Indonesia. The multidimensional model conceptualizes identity formation as a process unfolding across three dialectical axes: temporal (deconstruction, reconstruction, co-construction), social (individual, communal, national), and cultural (universality, locality, globality). The synthesized literature findings challenge Western-centered theoretical assumptions: Indonesian Muslims demonstrate multi-layered and intersecting categorizations, culturally meaningful identifications, and reflective comparisons that are contributory rather than competitive. This study advances decolonial Islamic thought by positioning Qur'an learning as an emancipatory epistemological praxis that transcends the anti-Western or pro-Western dichotomy. The Indonesian model shows how decolonization manifests in daily pedagogical practices rather than in abstract discourse, offering a replicable framework for global Muslim communities that negotiate authentic identity within postcolonial modernity without reproducing Western hegemony or reactive fundamentalism.